Access to Weapons: A Comparative Analysis Between Poland and the United States - Phillips, Brian; Frańczuk, Magdalena (Journal of Public Governance, 2021)
Objectives: In this article, we attempt to answer the following question: is there a need to liberalise policies and laws to allow the Polish citizens to have a greater access to weapons? We compare the Polish and the American regulations in this area. In our attempts to understand possible ramifications for Poland’s greater access to weapons, we review the American experience with firearms with emphasis on ownership history, the current debates, a comparative analysis of other dangers, and policy implications. In the conclusion, we employ the culture theory of risk to highlight the debates. The article draws attention to aspects meaningful in the context of shaping the policy of access to weapons and the direction of possible changes in legal regulations in this area.Research Design & Methods: The methods used in this article revolve round literature reviews of the debates, statistical data, a survey analysis, and an analysis of legal regulations.Findings: Restrictions on the access to weapons in Poland may not be desirable. They can limit civic rights and prevent a potential net gain of financial revenue. On the other hand, too liberal access to weapons can be potentially dangerous for the safety and well-being of the citizens.Implications / Recommendations: We believe that more research in this area needs to be conducted with a greater focus on the culture theory of risk as well as other paradigms which employ the latest statistics for a broader social-research agenda. We observe a lack of research and literature in this area.Contribution / Value Added: Given the current social and economic climate in Poland and in the United States, we find this research study to be both timely and important. Specifically, on December 14, 2019, new arms regulations entered into force in Poland. On the other hand, President Joe Biden has recently positioned himself on taking a more rigorous approach to firearm violence.Article classification: research articleJEL classification: K14, K19